Language Errors in Translation from Foreign Language into Russian in Written Works of University Students - G. A. Zhdanova; L. V. Almyashova (Научный диалог, 2018)
The problem of identifying and correcting language errors in the translation from a foreign language (German and English) into Russian in written works of students is considered. The question of one of the controversial problems in mastering foreign language speech, namely the attitude of teachers and students to grammatical, lexical and stylistic errors, is raised. It is noted that foreign and domestic methodologists have proved the position of error correction as an important element of foreign language teaching methods. The authors of the article pay attention to the work with errors at such a stage of learning as written speech. The article describes the importance of the analysis of language errors in written foreign language speech, as it allows to increase the level of literacy of part-time students in the performance of written tasks. Typical communicative mistakes of Russian-speaking students studying foreign languages are revealed. The article describes the long-term experience of foreign language teachers of a technical University with part-time students, which allows to assert that the work on errors is important not only for improving the language level of students, but also for the teacher. It is argued that the teacher should use error analysis for methodological and didactic developments intended for students.